Effects of Low Comment Engagement on Students’ Information Processing in Instagram Reviews - Herlina Herlina; Soraya Asnusa; Bandarsyah Bandarsyah (Universitas Darul Ulum, 2026)
The objective of this study is to analyze the influence of online reviews on college Instagram comments on prospective students’ decision- making processes through the integration of the Elaboration Likelihood Model (ELM) and Engel-Kollat-Blackwell (EKB) with an implicit issue: the low number of comments on Instagram posts is often viewed merely as a technical weakness in promotion, whereas this condition can influence digital persuasion mechanisms. The research gap lies in the limited number of studies specifically examining prospective students’ decisions within the context of low comment engagement, while the novelty of this study positions the low number of comments as a theoretical context that drives a shift from peripheral cues toward central processing. The research sample consisted of 250 respondents, comprising potential prospective students and followers of the official IIB Darmajaya Instagram account, selected via purposive sampling. Data were analyzed using SEM-PLS with the assistance of SmartPLS 3.0. The results indicate that perceived information and review credibility have a significant positive effect on trust; trust has a positive effect on attitude; attitude has a positive effect on intention; and intention has a positive effect on deciding on a university. Conversely, low comment engagement was found to negatively moderate all primary relationships, thereby weakening the decision-making process. Theoretically, this study expands the ELM and enriches the EKB within the context of digital higher education marketing. Practically, these results underscore the importance of informative, credible content and active comment interaction